2021
DOI: 10.1002/nau.24600
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of an automated dual‐arm instrumented intravaginal dynamometer

Abstract: Aims: (1) To present the design of a novel intravaginal dynamometer (IVD) capable of measuring vaginal closure force on both the anterior and posterior arms, (2) to use bench testing to validate the force, speed of arm opening, and positional accuracy of load measurement along the IVD arms, and (3) to present in vivo force measurements made with this device, comparing forces measured by the anterior and posterior arms. Methods: IVD load measurements were validated against an Instron® Universal Tester, arm open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…From the 101 records included, 23 PFM dynamometers from 15 research groups were identified. PFM dynamometers were grouped into two categories: clinical PFM dynamometers ( n = 20, from 12 research groups), 7–26 meant for research settings, and personal PFM dynamometers ( n = 3, from three groups), which were commercially available and intended for patient use 27–29 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the 101 records included, 23 PFM dynamometers from 15 research groups were identified. PFM dynamometers were grouped into two categories: clinical PFM dynamometers ( n = 20, from 12 research groups), 7–26 meant for research settings, and personal PFM dynamometers ( n = 3, from three groups), which were commercially available and intended for patient use 27–29 …”
Section: Resultsmentioning
confidence: 99%
“…Outcomes : rate of force development, number of contractions, peak force and normalized area under the curve between 10‐60s (Intraclass correlation coefficient) 12 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations